Metacognition ability of students through discovery learning practice guide on acid-base practicum - S Haryani; M H Amanda; S Wardani (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This research is aimed to analyze the students’ metacognition skills through practicum guide based on discovery learning in acid-base practicum. This research is a mixed method research which emphasis on quantitative and qualitative data collection that was done concurrently. Practicum guide arrangements were designed beginning with the selection of practicum materials, the arrangement of practicum guide content clues, the combination between learning content and syntax, expert validation, practicum trials and the analysis of trial data. Metacognition skills were measured through tests, questionnaires and interviews. Quantitative data were analyzed based on the metacognition skill percentage levels which were obtained from the test result. The research results showed the average scores of the test with metacognition indicators in the amount of 87, 94%, while the mean score of the questionnaire was 81.64%. Metacognition skill test level was low 17, 64%; moderate 61, 76%; and 20, 59% were at high levels. Based on the results, it was known that high-level students always realize what should be designed, be done, and feel capable to carry out the practicum. Thus, a practicum guide based on discovery learning can show the level of metacognition skill in every student.